Answer:
theres no question lol
Step-by-step explanation:
<h3>
Answer: Choice C</h3>
Started in Quadrant II and ended in Quadrant IV.
==========================================================
Explanation:
Refer to the diagram below. It shows how the four quadrants are labeled using roman numerals. We start in the upper right corner (aka northeast corner) and work counterclockwise when labeling quadrant I, II, III, and IV in that order.
The green point A is located in quadrant II in the northwest. Meanwhile point B in red is in the southeast quadrant IV.
Therefore, we started in <u>quadrant II</u> and ended in <u>quadrant IV</u> which points us to <u>choice C.</u>
Answer:

Step-by-step explanation:
<u>Question 1</u>
<u>Part (a)</u> :
⇒ 6 × 6 × 6 × 6 × 6 × 6 × 6 = 6ˣ
⇒ 6⁷ = 6ˣ
⇒ x = 7
<u>Part (b)</u> :
⇒ y² = 169
⇒ √y² = √169
⇒ y = ± 13
⇒ y = 13, y = -13
<u>Question 2</u>
<u>Part (a)</u> :
⇒ (√5)² × (√3)²
⇒ 5 × 3
⇒ 15
<u>Part (b)</u> :
⇒ (∛9)³ × (√30)²
⇒ 9 × 30
⇒ 270
Answer:
2/3
Step-by-step explanation:
Let's define z = x-y, so solving for z will tell us exactly what we want to know. Then we can substitute for x: x = z+y, and our equations become ...
7(z+y)+3y = 8 ⇒ 7z +10y = 8
6(z+y)-3y = 5 ⇒ 6z +3y = 5
We can eliminate the y-variable by subtracting 3 times the first equation from 10 times the second:
10(6z +3y) -3(7z +10y) = 10(5) -3(8)
60z +30y -21z -30y = 50 -24 . . . . eliminate parentheses
39z = 26 . . . . collect terms
z = 26/39 = 2/3 . . . . . divide by the coefficient of z and reduce
The value of x - y is 2/3.
_____
The attached graph shows (x, y) = (1, 1/3), so x - y = 1 - 1/3 = 2/3.